2003
DOI: 10.1002/prot.10316
|View full text |Cite
|
Sign up to set email alerts
|

A path from primary protein sequence to ligand recognition

Abstract: A novel method to organize protein structural information based solely on sequence is presented. The method clusters proteins into families that correlate with the three-dimensional protein structure and the conformation of the bound ligands. This procedure was applied to nicotinamide adenine dinucleotide [NAD(P)]-utilizing enzymes to identify a total of 94 sequence families, 53 of which are structurally characterized. Each of the structurally characterized proteins within a sequence family correlates to a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…10 Comparing clusters of sequences of NAD(P)-utilising enzymes from the SWISS-PROT database 11 with the conformations of bound cofactors, the main result reported is that each sequence family binds NAD(P) molecules in conformations which cluster together. This is not surprising, since the identification of protein relationships from sequence alone implies that more than 30% of their residues are identical, which in turn implies that function is conserved, and hence the cofactor should be expected to bind in the same way.…”
Section: Introductionmentioning
confidence: 95%
“…10 Comparing clusters of sequences of NAD(P)-utilising enzymes from the SWISS-PROT database 11 with the conformations of bound cofactors, the main result reported is that each sequence family binds NAD(P) molecules in conformations which cluster together. This is not surprising, since the identification of protein relationships from sequence alone implies that more than 30% of their residues are identical, which in turn implies that function is conserved, and hence the cofactor should be expected to bind in the same way.…”
Section: Introductionmentioning
confidence: 95%
“…NAD(P)(H)‐dependent enzymes are ubiquitous, and, from a large number of X‐ray structures, more than 10 different NAD(P)(H) binding folds can be identified, of which the Rossmann‐fold is the most common [3]. A recent study of enzyme–NAD(P)(H) complexes showed that the binding fold also correlates with the conformation of the NAD(P)(H) ligand [4]. The affinity for NAD(P)(H) can range from very tight binding, as in nicotinoproteins, which use the nucleotides as a cofactor [5], to weak binding, as is the case for p ‐hydroxybenzoate hydroxylase, an enzyme that does not have a recognizable NAD(P)H‐binding domain [6].…”
mentioning
confidence: 99%
“…Application of cofactor fingerprinting with STD NMR to dehydrogenases We initially applied the cofactor fingerprinting with STD NMR approach to well-characterized proteins (dehydrogenases), then to a protein of unknown function, as part of a lar- ger functional proteomics project [12][13][14][15]. Dehydrogenases are an excellent gene family for applying functional proteomic methods, since they represent 3-6% of most proteomes, and are easily identified using bioinformatics tools [16,17]. But, it is often difficult to predict based on sequence whether there will be preference for NADH or for its 2 0 -phosphorylated form (NADPH).…”
Section: Resultsmentioning
confidence: 99%
“…Dehydrogenases are an excellent gene family for applying functional proteomic methods, since they represent 3-6% of most proteomes, and are easily identified using bioinformatics tools [16,17]. But, it is often difficult to predict based on sequence whether there will be preference for NADH or for its 2 0 -phosphorylated form (NADPH).…”
Section: Application Of Cofactor Fingerprinting With Std Nmr Tomentioning
confidence: 99%